2015
DOI: 10.1515/afmnai-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Dexmedetomidine and Midazolam on Sedation in Children with Head Trauma to Perform CT in Emergency Department / Upoređivanje efekata deksmedetomidina i midazolama na sedaciju dece sa povredom glave radi snimanja CT-om na Odeljenju urgentne medicine

Abstract: Many of the children referred to the emergency complain of head trauma. Children usually require sedition to reduce their failure and fear because of high activity and fear of performing computed tomography (CT). Dexmedetomidine and Midazolam belong to short-acting drugs for this purpose. This study aimed to compare the effect of the above mentioned drugs on sedition in children.Children referred to the emergency department were randomly divided into two groups. Group A was sedated with 0.05 mg/kg IV Midazolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Study designs included 11 RCTs, 22,32–41 13 cohort studies and other nonrandomized studies, 19–21,23,42–50 and 11 case series and case reports 12,51–60 . Six of the included studies were conference abstracts 20,21,40,47,50,56 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study designs included 11 RCTs, 22,32–41 13 cohort studies and other nonrandomized studies, 19–21,23,42–50 and 11 case series and case reports 12,51–60 . Six of the included studies were conference abstracts 20,21,40,47,50,56 .…”
Section: Resultsmentioning
confidence: 99%
“…Intranasal DEX appeared to perform as well as or better than intranasal midazolam for this indication (faster onset of sedation in one trial, 41 no difference in rate of adequate sedation or need for rescue medications in another 35 ). A prospective open-label study demonstrated universally successful sedation for CT imaging in pediatric patients with intranasal DEX, 42 a small retrospective chart review found that DEX facilitated completion of imaging in 86% of adult patients, 21 and four patients in a small pediatric case series were successfully sedated for various imaging tests with intramuscular DEX.…”
Section: Sedation To Facilitate Radiologic Imagingmentioning
confidence: 95%
See 2 more Smart Citations